Genetic polymorphisms of DPYD in patients with breast cancer on capecitabine therapy - Abbas, Raaid Fadhl; Sahib, Ahmed Salih; Mahmood, Hasanain Shakir; Mohsin, Karar Kadhim; Majeed, Ali Amal Aldeen (Journal of Contemporary Medical Sciences, 2023)
Objectives: Breast cancer is the primary cause of death in Iraqi women aged 30–54 years. The study examined the relationship between (G > A) (rs3918290) and (rs55886062, T >G) DPYD gene polymorphisms, their haplotypes, and capecitabine serum concentrations in postmenopausal Iraqi women with breast cancer in postmenopausal women. During capecitabine chemotherapy. Methods: The study included 200 women: 100 apparently health (45-75 years old) and 100 with breast cancer (40-70 years old). This study, conducted between July and October 2022 at the oncology centre at Imam al-Hussain medical city in Kerbala, Iraq, plasma levels of Capacetabine and 5fu were measured in breast cancer patients who had been taking capecitabine for at least three months. All participants gave informed consent. Results: Capecitabine, and 5FU concentrations in breast cancer patients differed significantly, As the results showed, Capecitabine, and 5FU had a significantly higher concentration of them in patients with the TT allele than in those with the CC and CT alleles for the polymorphism (IVS14 + 1G > A) (rs3918290) and in patients with DPYD*13 (rs55886062) with the CC allele rather than the AA and AC alleles. Mutant allele carriers had increased Capecitabine concentrations (p<0.001). Conclusion: Ca15.3, serum calcium, and estradiol all exist in bodily serum, making them a potentially useful novel diagnostic biomarker for patients with breast cancer due to their high levels of stability, as well as the biological properties of tumors, such as serum calcium and estrogen.